First record of Halocercus sp. (Pseudaliidae) lungworm infections in two stranded neonatal orcas (Orcinus orca). Issue 12 (25th April 2018) - Reckendorf, A.; Ludes-Wehrmeister, E.; Wohlsein, P.; Tiedemann, R.; Siebert, U.; Lehnert, K.
Abstract: Orca ( Orcinus orca ) strandings are rare and post-mortem examinations on fresh individuals are scarce. Thus, little is known about their parasitological fauna, prevalence of infections, associated pathology and the impact on their health. During post-mortem examinations of two male neonatal orcas stranded in Germany and Norway, lungworm infections were found within the bronchi of both individuals. The nematodes were identified as Halocercus sp. (Pseudaliidae), which have been described in the respiratory tract of multiple odontocete species, but not yet in orcas. The life cycle and transmission pathways of some pseudaliid nematodes are incompletely understood. Lungworm infections in neonatal cetaceans are an unusual finding and thus seem to be an indicator for direct mother-to-calf transmission (transplacental or transmammary) of Halocercus sp. nematodes in orcas.